The white magic five and dime [large type] : a tarot mystery - Hockensmith, Steve (Hockensmith, Steve. Tarot mystery., 2014)
Much to Alanis McLachlan's surprise, her estranged con-woman mother has left her an inheritance: The White Magic Five & Dime in tiny Berdache, Arizona. Reluctantly claiming it, Alanis decides to stay and try to find out how her mother died. With help from a hunky cop and her mother's live-in teenage apprentice, Alanis begins faking her way through tarot readings. But the more she uses the deck, the more Alanis begins to find real meaning in the cards . . . and the secrets surrounding her mother's demise.